ChemInform Abstract: Cycloisomerization of 2‐Alkynylanilines to Indoles Catalyzed by Carbon‐Supported Gold Nanoparticles and Subsequent Homocoupling to 3, 3′‐Biindoles. Issue 14 (8th April 2014) - Perea‐Buceta, Jesus E.; Wirtanen, Tom; Laukkanen, Otto‐Ville; Maekelae, Mikko K.; Nieger, Martin; Melchionna, Michele; Huittinen, Nina; Lopez‐Sanchez, Jose A.; Helaja, Juho
Abstract The cycloisomerization of 2‐alkynyl substituted anilines (I) is studied using a heterogeneous gold on carbon catalysts.